The basics of communicative genological analysis - Siekiera, Rafał (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter presents the most important assumptions of the new method of speech genres research. It can be included in the area of ​​linguistic genology, and is based on communicative grammar. The basis of the method is the assumption that the genre of utterance can be perceived as a standard scenario, including both the circumstances of creating the text and its structure, typical participants of communication acts in which the text appears, or elements constituting signals that trigger the script during the reception and interpretation of the utterance. This allows the researcher to characterize given scenario and to identify deviations from it in specific texts. Textual representations of genres can also be studied on three levels of communication (distinguished by Michael Halliday, and then also by communicativists): ideational, interactive and textual.